Validitas Media Belajar Gerbang Logika Berbasis Praktikum pada Mata Kuliah Elektronika Dasar dengan Pendekatan Saintifik - Pertiwi, Novia Ayu Sekar; Fauziyah, Anis; Husna, Asiyah Lu’lu’ul (JoEMS (Journal of Education and Management Studies), 2023)
Almost every human activity cannot be separated from digital electronic equipment. Digital electronics is not only used for computers or smartphones, but has also spread to household appliances, vehicles, health equipment and others. One of the theories studied in the Basic Electronics Practicum which is closely related to the current development of digital technology and is used in everyday life is logic gates. Basic logic gates consist of seven types, namely AND, OR and NOT, NAND, NOR, X-OR and X-NOR logic gates. Current conditions, the Unwaha Physics Education study program does not yet have a logic gate practicum tool so students cannot carry out basic logic gate practicum. Therefore, basic logic gate practicum tools are needed and students can carry out the practicum actively. These things are the background for developing practical media with a scientific approach. This means that students must be actively involved in carrying out practicums. In order for the practicum media to be used in learning, the tool must be valid so its validity needs to be tested by experts. The validation results by material experts and media experts were declared valid and can be used in learning because the average percentage in media validation showed a value of 96.07% and the average percentage in material validation showed a value of 87.09%. Both validation results are included in the very good criteria.